3D-C-Fe4N@NiCu/Metallic macroporous frameworks for binder-free compact hybrid supercapacitors with high areal capacities. (1st February 2023) - Mohanty, Ankita; Balasubramaniam, Saravanakumar; Ramadoss, Ananthakumar
Highlights: 3D-NiCu network over various substrates: Cu, SS and Ti are constructed via DHBT. 3D-NiCu are coated with carbon-doped iron nitride via vapor phase growth process. Binder-free 3D porous negative electrodes are successfully fabricated. 3D-C-Fe4 N@NiCu/Cu delivered CA of 2118 mC/cm 2 with 92% cycling stability. 3D-Co3 O4 /Ni‖3D-C-Fe4 N@NiCu/Cu delivered better energy storage performance. Abstract: In the present research work, binder-free three-dimensional nickel-copper (3D-NiCu) over various substrates copper (Cu), stainless steel (SS) and titanium (Ti) were synthesized via dynamic hydrogen bubble template (DHBT) method and further deposited by carbon-doped iron nitride (C@Fe4 N) electroactive material via vapor phase growth method to form 3D-C-Fe4 N@NiCu/Cu, 3D-C-Fe4 N@NiCu/SS, and 3D-C-Fe4 N@NiCu/Ti electrodes, respectively. Unveiling the maximum performance among the three electrodes, 3D-C-Fe4 N@NiCu/Cu delivered a high areal capacity value of 2118 mC/cm 2 at 3 mA/cm 2 current density along with 92% capacity retention. Further, the assembled hybrid supercapacitor(HSC) based on 3D-Co3 O4 /Ni‖3D-C-Fe4 N@NiCu/Cu HSC delivered the best electrochemical performance including wide potential window (1.5 V), specific capacity and cycling stability (89%) among the three HSCs. The results conclude that the novel synthesis strategy of vapor phase growth over 3D bi-metallic templates, opens up a new avenue, towards the formation of reliable and competitive HSC negative electrodes over a range of metal substrates, divergent from conventional carbon-based negative electrodes, which is extendable to other metals and applications. Graphical abstract: Image, graphical abstract